Policy Capacity for Health Reform: Necessary but Insufficient; Comment on "Health Reform Requires Policy Capacity" - Owen Adams (Kerman University of Medical Sciences, 2016)
Forest and colleagues have persuasively made the case that policy capacity is a fundamental prerequisite to health reform. They offer a comprehensive life-cycle definition of policy capacity and stress that it involves much more than problem identification and option development. I would like to offer a Canadian perspective. If we define health reform as re-orienting the health system from acute care to prevention and chronic disease management the consensus is that Canada has been unsuccessful in achieving a major transformation of our 14 health systems (one for each province and territory plus the federal government). I argue that 3 additional things are essential to build health policy capacity in a healthcare federation such as Canada: (a) A means of "policy governance" that would promote an approach to cooperative federalism in the health arena; (b) The ability to overcome the "policy inertia" resulting from how Canadian Medicare was implemented and subsequently interpreted; and (c) The ability to entertain a long-range thinking and planning horizon. My assessment indicates that Canada falls short on each of these items, and the prospects for achieving them are not bright. However, hope springs eternal and it will be interesting to see if the July, 2015 report of the Advisory Panel on Healthcare Innovation manages to galvanize national attention and stimulate concerted action.